Determination and validation of hupehenine in rat plasma by UPLC‐MS/MS and its application to pharmacokinetic study. (1st June 2015) - Wen, Congcong; Wang, Shuanghu; Huang, Xueli; Liu, Zezheng; Lin, Yingying; Yang, Suping; Ma, Jianshe; Zhou, Yunfang; Wang, Xianqin
Abstract In this work, a sensitive and selective ultra‐performance liquid chromatography–tandem mass spectrometry (UPLC‐MS/MS) method for determination of hupehenine in rat plasma was developed and validated. After addition of imperialine as an internal standard (IS), protein precipitation by acetonitrile–methanol (9:1, v/v) was used to prepare samples. Chromatographic separation was achieved on a UPLC BEH C18 column (2.1 × 100 mm, 1.7 µm) with 0.1% formic acid and acetonitrile as the mobile phase with gradient elution. An electrospray ionization source was applied and operated in positive ion mode; multiple reaction monitoring mode was used for quantification using target fragment ions m/z 416.3 → 98.0 for hupehenine, and m/z 430.3 → 138.2 for IS. Calibration plots were linear throughout the range 2–2000 ng/mL for hupehenine in rat plasma. Mean recoveries of hupehenine in rat plasma ranged from 92.5 to 97.3%. Relative standard deviations of intra‐day and inter‐day precision were both <6%. The accuracy of the method was between 92.7 and 107.4%. The method was successfully applied to a pharmacokinetic study of hupehenine after either oral or intravenous administration. For the first time, the bioavailability of hupehenine was reported as 13.4%. Copyright © 2015 John Wiley & Sons, Ltd.